(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
According to the International Federation of Robotics, the number of industrial robots installed in factories increased 60% in 2024. This rapid rise means that more than ever, industrial designers will need components that can provide the necessary speed, reliability, operational life, and varied switching abilities robotics require. If you visit a modern factory and observe the amazing electronics at work in an assembly cell, you’ll see a variety of sensors on display. Most of these sensors have separate wires for positive voltage supply, ground and signal. Applying power allows a sensor to do its job, whether that’s observing the presence of ferromagnetic metals nearby or sending a light beam out as part of the facility’s security system. The humble mechanical switches that trigger these sensors, like the reed switch, only need two wires to do their jobs. These switches activate using magnetic fields. Industrial Manufacturing and Robotics: The Benefits of Designing in Reed Switches, Relays, and Sensors reviews the structural and safety advantages that make reed technology ideal for the industrial sector. When exposed to a magnetic field (from a magnet, solenoid), oriented in a certain way, contacts made of ferromagnetic materials begin to move (close, open, switch, depending on the type of reed switch).